2010
DOI: 10.1119/1.3488097
|View full text |Cite
|
Sign up to set email alerts
|

Listening to student conversations during clicker questions: What you have not heard might surprise you!

Abstract: When instructors provide time for students to discuss their ideas in Peer Instruction, instructors minimally expect that the conversation partners will discuss their opinions relating to the physical attributes posed in a question and submit clicker responses that coincide with individual opinions. We defined conversations that met these two criteria as "standard conversations." In our study of 361 recorded Peer Instruction conversations from large introductory astronomy classrooms taught by experienced instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 19 publications
1
54
2
7
Order By: Relevance
“…For example, James and Willoughby (2011) recorded peer conversations in introductory university-level astronomy courses to determine whether students had ''standard conversations,'' which were defined as involving at least one student in a peer group discussing a minimum of one multiple-choice answer and the student answers were aligned with the articulated ideas of the group. They chose this definition because it matched the idealized productive conversations imagined by the course instructors.…”
Section: Learning Benefits Of Peer Discussion During Clicker Questionsmentioning
confidence: 99%
“…For example, James and Willoughby (2011) recorded peer conversations in introductory university-level astronomy courses to determine whether students had ''standard conversations,'' which were defined as involving at least one student in a peer group discussing a minimum of one multiple-choice answer and the student answers were aligned with the articulated ideas of the group. They chose this definition because it matched the idealized productive conversations imagined by the course instructors.…”
Section: Learning Benefits Of Peer Discussion During Clicker Questionsmentioning
confidence: 99%
“…Alguns trabalhos tiveram como foco elementos específicos do método, focando no(a): tipo de sistema de votação utilizado [100]; tipo de interação que ocorre na etapa de discussão entre os colegas [94,[101][102][103]; importância das atividades préviasàs aulas [87]; tempo de submissão das respostas dos estudantes [104]; apresentação dos resultados da primeira rodada de votação [105,106]; relação entre a localização dos estudantes e a distribuição de repostas [107]. Além disso, um dos trabalhos encontrados nesta revisão almejou construir uma expressão analítica que revela a correlação entre a taxa de acertos, nos Testes Conceituais, dos estudantes antes e após a discussão entre os colegas [108].…”
Section: Pesquisas Referentes Aos Elementos Que Compõem O Piunclassified
“…Ambas as propostas se mostraram frutíferas para promover o engajamento dos estudantes. Já James e Willoughby [103] buscaram categorizar os tipos de interação que acontecem na etapa de discussão com os colegas. Através da análise das interações dos estudantes, os autores encontraram, em muitos casos, discussões pouco frutíferas (devidoà baixa compreensão dos Testes Conceituais), levando a interpretação de que as questões utilizadas não providenciaram um feedback efetivo da aprendizagem dos estudantes.…”
Section: Pesquisas Referentes Aos Elementos Que Compõem O Piunclassified
See 1 more Smart Citation
“…The majority of this research has demonstrated positive impacts of ARSs on enhancing learning outcomes (Voelkel & Bennett, 2014), bolstering students engagement (Kotevski, 2014;Dunn, Richardson, Oprescu, & McDonald, 2013), improving students' attendance (e.g., James & Willoughby, 2011), stimulating peer and in-class discussion (Pelton & Pelton, 2006), and encouraging students to believe that these devices can aid them in identifying misunderstandings of learning concepts (Bode et al, 2009). Research has also revealed that the use of ARS in classrooms has been inextricably linked to students' emotional, motivational, and cognitive classroom experiences (Simpson & Oliver, 2007).…”
Section: The Efficacy Of Traditional Arssmentioning
confidence: 99%